RETRACTED: Exosomes From Cancer-Associated Mesenchymal Stem Cells Transmit TMBIM6 to Promote the Malignant Behavior of Hepatocellular Carcinoma via Activating PI3K/AKT Pathway - Shang, Chuzhi; Ke, Mi; Liu, Lin; Wang, Cong; Liu, Yufang; Zheng, Xin (Frontiers in Oncology, 2022)
Objective: Cancer-associated mesenchymal stem cells (MSCs) regulate the progression of cancers through exosome-delivered components, while few studies are conducted in hepatocellular carcinoma (HCC). This study aimed to evaluate the effect of exosomes from HCC-associated MSCs (HCC-MSCs) on HCC cellular functions and the potential regulatory mechanism. Methods: HCC cells (Huh7 and PLC) were cultured normally, or co-cultured with HCC-MSCs, HCC-MSCs plus GW4869 or HCC-MSCs derived exosomes; then mRNA sequencing and RT-qPCR validation were conducted. Subsequently, candidate genes were sorted out and modified in HCC cells. Next, TMBIM6 modified HCC-MSCs were used to treat HCC cells. Results: Both HCC-MSCs and their derived exosomes promoted proliferation, invasion, sphere formation ability but suppressed apoptosis in HCC cells (all P<0.05); however, the effect of HCC-MSCs on these cellular functions was repressed by exosome inhibitor (GW4869). Subsequently, TMBIM6, EEF2 and PRDX1 were sorted out by mRNA sequencing and RT-qPCR validation as candidate genes implicated in the regulation of HCC cellular functions by HCC-MSCs derived exosomes. Among them, TMBIM6 had a potent effect (all P<0.05), while EEF2 and PRDX1 had less effect on regulating HCC cell viability and invasion. Next, direct silencing TMBIM6 repressed viability, sphere formation, invasion, EMT and PI3K/AKT pathway but promoted apoptosis in HCC cells; however, overexpressing TMBIM6 showed the opposite effect. Furthermore, incubating with exosomes from TMBIM6-modified HCC-MSCs presented a similar effect as direct TMBIM6 modification in HCC cells. Conclusion: HCC-MSCs derived exosomes transmit TMBIM6 to promote the malignant behavior via PI3K/AKT pathway in HCC.